The Assessment of the Education Laboratory Performance by Using Balanced Score Card Method - Nurhasnah, Nurhasnah; Eliza, Rivdya (AT-TALIM, 2017)
This Research was conducted to measure the performance quality of the educational laboratories at the faculty of Islamic Education and Teacher Training in State Islamic University or UIN Imam Bonjol Padang, especially in the performance of the field Practice for Teacher Training laboratory (PPL), Computer and Islamic Education Practice Laboratory (PPAI) by using balanced score card method. In term of the method, four perspectives were used such as: financial perspective, customers (the users) perspective, internal business perspective, and growth and learning process. The foci of this study included: PPL, computer, and PPAI. The subjects of this research were 3 heads of the labors, 6 laboratory staff, 3 financial staff, and 90 students who were studying in semester VII at faculty of Islamic Education and Teacher Training in UIN IB Padang at academic year 2016/2017. Questionnaire, interview guide, and observation sheet were used as the instruments that have been tested their reliability and validity. Data analysis was employed by measuring the customer perspective questionnaires, internal business process perspective, and learning growth perspective. The finding of the study showed that the performance of labor the PPL laboratory is 3.27 (65.35%) with good category. The Performance of computer laboratory is 3.05 (61%) with good category. The Performance of the PPAI laboratory was 2.76 (55.2%) with less good category. Overall, all three laboratory have 3.03 (60.6%) performance measurement result   with good category.